2006
DOI: 10.1007/s10565-006-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 phosphorylation correlates with hydroquinone-induced alterations in myeloid differentiation and cytokine-dependent clonogenic response in human CD34+ hematopoietic progenitor cells

Abstract: The transcriptional regulatory factor PU.1 is important for the regulation of a diverse group of hematopoietic and myeloid genes. Posttranslational phosphorylation of PU.1 has been demonstrated in the regulation of a variety of promoters in normal cells. In leukemia cells, differing patterns of PU.1 phosphorylation have been described among acute myelogenous leukemia (AML) subtypes. Therefore, we hypothesized that modulation of PU.1-dependent gene expression might be a molecular mediator of alterations in myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Both animal models and in vitro human cell cultures demonstrated that hydroquinone and para-benzoquinone are the active metabolites of benzene [ 15 , 16 ]. Additionally, it was shown that hydroquinone induces cell changes that are consistent with various cellular changes known to mark the early progression of AML in humans [ 16 , 17 ]. These molecular-level studies supported available human in vivo data (i.e., standard epidemiological studies), thereby lessening the need for additional observational studies to support a causal relationship.…”
Section: Criteria 2: Consistencymentioning
confidence: 95%
“…Both animal models and in vitro human cell cultures demonstrated that hydroquinone and para-benzoquinone are the active metabolites of benzene [ 15 , 16 ]. Additionally, it was shown that hydroquinone induces cell changes that are consistent with various cellular changes known to mark the early progression of AML in humans [ 16 , 17 ]. These molecular-level studies supported available human in vivo data (i.e., standard epidemiological studies), thereby lessening the need for additional observational studies to support a causal relationship.…”
Section: Criteria 2: Consistencymentioning
confidence: 95%
“…HQ-induced dysregulation of external signals modulating the protein phosphorylation of the transcriptional regulator, PU.1, may promote the clonal proliferation of CD34þ cells (187). HQ was shown to alter the pattern of binding of PU.1 to DNA in a time-and Mechanism of benzene-induced leukemia dose-dependent manner and to induce hyperphosphorylation of the PU.1 protein, in cultured human CD34þ cells.…”
Section: Dysregulation Of the Hsc Niche Leads To Increased Proliferationmentioning
confidence: 97%
“…t (15,17), t (8,21), Flt3 mutations) were associated with decreased PU.1 expression in AML M3 and in some cases of AML M2; [20][21][22][23] (c) PU.1 protein hyperphosphorylation was observed in some subtypes of AML. 24 Iron et al 25 exposed human CD34 þ to hydroxyquinone, a benzene metabolite, and found a marked PU.1 hyperphosphorylation, associated with an enhanced clonogenic activity and a block in myeloid differentiation. These studies could eventually explain the link between chronic exposure to high concentrations of benzene and AML development; (d) recently, two transcription factors of the Jun family were identified as PU.1 target genes.…”
Section: Introductionmentioning
confidence: 99%